PENINGKATAN KREATIVITAS DAN PEREKONOMIAN WARGA DENGAN DIVERSIFIKASI WORTEL MENJADI KERUPUK WORTEL DI DESA LOSARI KECAMATAN SUMOWONO KABUPATEN SEMARANG - Fahmi Arifan; Wisnu Broto; Nanik Kartikasari; Edy Supriyo; Alif Nur Fauzi Prasetyo; Susi Lestari; Tumiar Iriana (Sekolah Vokasi Universitas Diponegoro, 2023)
Losari is a village in Sumowono District, Semarang Regency, Central Java Province, Indonesia. This village is located on the slopes of Mount Ungaran, do not be surprised if the temperature around the village is cold. Losari Village is also known as an agropolitan village because of its abundant potential for agricultural products, especially vegetables. One of the abundant vegetable production is carrots. Carrots that are ready for harvest are usually sold directly by farmers to middlemen and traders in the market. So there is no diversification of processed products from carrots which are made into other processed food products that have a higher value than selling fresh carrots. Especially when there is an abundance of carrot production in the village, the selling price of carrots is very cheap. So the creativity of the residents is needed in diversifying processed food products from carrots. One way is to process carrots into carrot crackers. Carrot crackers have high nutritional value. It is hoped that the diversification of processed carrot cracker food products will increase creativity in processing natural resources independently in the village and the economy of local residents. Slicer is a slicing tool that can cut ingredients such as cracker dough in large quantities and in a short time. It is hoped that with this slicer the slicing of the cracker dough can take place quickly, practically and hygienically.